2021
DOI: 10.1002/admi.202002241
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Citric Acid/RGD Multilayers on Mg‐Zn‐Y‐Nd Alloy via Layer‐by‐Layer Self‐Assembly for Promoting Surface Biocompatibility

Abstract: Magnesium (Mg) alloy, an important biodegradable material widely investigated on cardiovascular stent, is restricted for further application due to some limited functions, such as the excessively rapid degradation rate, poor hemocompatibility, and delayed re‐endothelialization. To overcome these shortcomings, surface modification with biomolecules has attracted much attention. In this study, the multifunctional coatings of citric acid (CA) and Arg‐Gly‐Asp (RGD) via layer‐by‐layer self‐assembly are immobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…After the washing step, the samples were dehydrated gradually using 25%, 50%, 75%, and 100% ethanol solution. During a complete drying step and spraying gold treatment, the platelets adherent on the samples were observed by SEM; the numbers of the platelets adherent on each sample were counted according to the previous report [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…After the washing step, the samples were dehydrated gradually using 25%, 50%, 75%, and 100% ethanol solution. During a complete drying step and spraying gold treatment, the platelets adherent on the samples were observed by SEM; the numbers of the platelets adherent on each sample were counted according to the previous report [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the biodegradable alloy of Mg-Zn-Y-Nd was coated with successive layers of polydopamine, citric acid, and Arg-Gly-Asp (RGD) peptide. The surface that was created is hemocompatible and allows for endothelization, while inhibiting smooth muscle cell adhesion and proliferation, overall improving the biocompatibility of the Mg alloy stents [ 105 , 106 ]. Extensive reviews of the role of citric acid as a crosslinker can be found in references [ 107 , 108 ].…”
Section: Citric Acid In Formulationsmentioning
confidence: 99%
“…Therefore, in the use of RGD modification, in addition to considering the conformation and density of RGD peptide, combined with anticoagulant substances is also a factor to be considered. 116 Layer-by-layer self-assembly 115 REDV Specifically bind to integrin α4β1 on the ECs. 117 Covalent grafting [118][119][120] 1.…”
Section: Peptidementioning
confidence: 99%